The relationship between occupational stressors and insomnia in hospital nurses: The mediating role of psychological capital - Wang, Mei-Fang; Shao, Pei; Wu, Chao; Zhang, Lin-yuan; Zhang, Lan-fang; Liang, Juan; Du, Juan (Frontiers in Psychology, 2023)
Background Nurses have a high incidence of insomnia. Insomnia not only damages the physical and mental health of nurses, but also reduces their productivity and quality of care, ultimately affecting patient care. Over the past 30 years, a large number of epidemiological surveys have shown that insomnia in nurses is associated with occupational stress. As an external feature of the role of a nurse, occupational stress is difficult to alter in a short period of time. Therefore, it is necessary to discuss the complex mediating variables in the relationship between occupational stress and insomnia in nurses in order to find different ideas to address the problem of insomnia caused by occupational stress. Psychological capital, the positive psychological strength of an individual, has been widely used in previous reports as a mediating variable between occupational stress and adverse psychological problems. Objective This study aimed to explore the mediating effect of psychological capital on occupational stressors and insomnia among Chinese nurses. Methods The Strengthening the Reporting of Observational Studies in Epidemiology statement was referred to conduct the study. A cross-sectional stratified sampling method was used to recruit 720 participants from a tertiary hospital in Jinan, Shandong province, located in the east of China, from June to August 2019. Questionnaires were used to obtain data on demographic variables, psychological capital, occupational stressors, and insomnia. Results The study findings revealed that work settings [department (F = 3.08, p = 0.006), working hours per week (t = −2.03, p = 0.043) and shift work (t = 3.66, p < 0.001)], decision latitude (r = −0.25, p < 0.001), psychological job demand (r = 0.15, p < 0.001), social support (r = −0.31, p < 0.001), and psychological capital (r = −0.40, p < 0.001) were differentially associated with insomnia experiences. This cross-sectional survey showed that psychological capital has significant mediation effects on the relationship between occupational stressors and insomnia. In the model of decision latitude - psychological capital - insomnia, the mediating effect was-0.04 (95%CI: −0.07 ~ −0.02), accounting for 50.0% of the total effect; In the model of job demands – psychological capital – insomnia, the mediating effect was 0.03 (95%CI: 0.01 ~ 0.06), accounting for 25.0% of the total effect; In the model of social support - psychological capital - insomnia, the mediating effect was −0.11 (95%CI: −0.16 ~ −0.07), accounting for 39.0% of the total effect. Conclusion Psychological capital not only had a direct effect on both occupational stressors and insomnia, but also played mediating roles in relationship between occupational stressors and insomnia. It has been suggested that nurses themselves and nursing managers should improve the psychological capital of nurses by various means to alleviate the effects of occupational stress on nurses’ insomnia.